PSYCHOLOGICAL DOMINICITY OF INTERPRETATION OF TEXTS OF THE INTERNET - Akimova, Nataliia (PSYCHOLOGICAL JOURNAL, 2019)
The psychological differences in the internet texts understanding are analysed in the article taking into account the classical and modern developments in the field of psychology of understanding and psychology of the Internet. For this theoretical methods and techniques were used: deductive and inductive methods, analysis and synthesis, generalization and systematization, as well as modeling. In addition, interpretation methods were used based on specific principles of the system, activity, cognitive and organizational approaches. It is noted that these differences in the Internet text understanding are due to the peculiarity of the object, the subject and the system of external expression. It is accentuated that an object on the Internet is a virtual world with its technical specifics. The subject on the Internet is in special conditions limiting sensory experience only to visual and auditory, a specific feeling of space and time, in a state of “continuous distracted attention”, “constant loading”, the permanent fixation of cyber activity results, the appearance of negative emotions with limited access to cyberspace, plurality of personality, “browsing”, virtual identity, disinhibition “online I”, leveling statuses, unlimited availability of contacts, changes priority and behaviour, in the conditions of “a bubble of filters”. The Intent text is also significantly different from the printed or oral, it is essentially a pragmatically integral electronic document, consisting of conditionally completed text blocks in the form of “windows”, and it has specific characteristics. The internet text understanding is like speech activity in general has three aspects: motivational, target and executive. The motivation to use the Internet often is distorted by the deformation of the needs of the Internet world, and also because the Internet sometimes acts as a compensatory environment. The instrument of performing the speech activity on the Internet are texts. And the result of internet text understanding is the secondary text of the recipient, that is a reaction text reading. The Internet texts understanding includes operations of reception, concentration, ignoring, thinking actions and operations (analysis and synthesis, comparison, abstraction and generalization), memory actions and operations (memorization, preservation, reproduction and forgetting), interiorization, sense-making and semantic syntax, evaluation, emotional identification and awareness. These actions and operations are distributed between the three stages of understanding: reception (perception of the external form of the text), interpretation (rational interpretation of the internal content of the text), emotional identification (establishment of emotional connotations and their awareness). But it should be noted that interpretation and emotional identification occur in parallel and can influence each other, affect the result.